Edukasi Hipertensi Pada Mayarakat di Masa Pandemi Covid-19 Desa Porame Dusun II Kecamatan Kinovaro: Edukasi Hipertensi Pada Mayarakat di Masa Pandemi Covid-19 Desa Porame Dusun II Kecamatan Kinovaro - Ibrahim kadir; Elsa yulianti; Uci via delfita lari; ludwika gracella; siskah maudy putri; Abd. Gani; Mutmainnah; Sry djulianty; Nurma’iya; Rizkhi amalia; Nilam sari; Siti hasmayuni; Arianto K ahmad; Meylani A'naabawati (CV. Multi Kreasi Media, 2022)
Hypertension is an abnormal increase in blood pressure, namely an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. Hypertension leads to cardiovascular diseases including heart disease, stroke and kidney problems. As for the results of data from the Kinovaro Health Center, hypertension is one of the three biggest diseases in the work area of ​​the Kinovaro Health Center. The purpose of giving about hypertension is one of the prevention efforts by increasing public knowledge and awareness of a healthy lifestyle that can affect health conditions, especially in the era of the COVID-19 pandemic. The method used in this community service activity is lectures and discussions (following the health protocol in the era of the covid-19 pandemic) using leaflet media. The results of the data show that most of the people in Porame Dusun II Village have an elementary school education level of 48%. The level of public knowledge about hypertension before being given education (pre-test) was 61% who did not know how to prevent hypertension, after being given education on the results of post-test data as much as 87% of the community had understood about preventing hypertension and managing a lifestyle for people with hypertension.